Denunciators in the National Socialist “Double State” - Kulesza, Jan; Kulesza, Witold (Studia Iuridica Toruniensia, 2023)
After the seizure of power by the National Socialists in Germany, denunciation to the new power spread to all strata of society. It was a way to prove loyalty to new authorities and to remove all insubordinate individuals who did not deserve participation in the national community due to insufficient enthusiasm for national revival. Denunciations resulted in various consequences, from removal from clerical work, through prison, concentration camp, to death. After the fall of the Third Reich, under the law enacted by the Allies, denunciators were held responsible for aiding and, in one case, for murder, when the denunciation led to the death penalty. However, from 1947 and 1948, based on the views of the doctrine of criminal law, efforts were made, using various arguments, to free denunciators from criminal liability. This aim was achieved with the Federal Republic of Germany, through its courts, fully supporting the practice of the judiciary of the Third Reich, adopting, in fact, the same approach, both with regard to the convictions of the denounced and the assessment of the conduct of the denunciators.